The Journey After the Journey: Family Counselling in the Context of Immigration and Ethnic Diversity - Grant, Karen J.; Henley, Arden; Kean, Mary (Canadian Journal of Counselling and Psychotherapy, 2007)
The development and implementation of a specific model for providing family counselling to immigrant and refugee families is examined. Conjointly developed by staff at a non-profit agency in the settlement and integration sector, and a team of consulting family therapists, the Multiple Partnership Model arose from community-based work and the demonstrated need for equitable and accessible counselling in languages other than English. The influence of narrative theory in its ability to address the challenges of ethno-cultural diversity and the imbalances of power inherent in cross-cultural counselling are discussed. As well, the dynamics of a co-therapy partnership between ethno-specific settlement counsellors acting as bi-cultural consultants and an on-site family therapist are highlighted. The specific workings of this partnership are outlined and case examples provided.